PENGARUH WORK-LIFE BALANCE DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN - Dewi Hertika; Ima Andriyani; Sari Sakarina (Fakultas Ekonomi Universitas IBA, 2026)
This study aims to analyze the effect of Work-Life Balance and Employee Engagement on employee performance with job satisfaction as an intervening variable at five private banks in Palembang. Amidst the dynamics of the banking industry that demands high productivity, a deep understanding of employee well-being and emotional engagement is crucial to maintaining organizational performance. The research method used was quantitative. The population in this study amounted to 340 employees. The sampling technique used simple random sampling with the determination of the sample size using the Slovin formula at a 10% error rate, resulting in a total of 77 respondents. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to comprehensively examine the relationships between variables. The results showed that Work-Life Balance and Employee Engagement have a positive and significant effect on job satisfaction, which in turn significantly impacts employee performance. The R2 value for the job satisfaction variable was 0.898, indicating that 89.8% of the variation in job satisfaction can be explained by Work-Life Balance and Employee Engagement. Meanwhile, the R2 value for employee performance reached 0.951, indicating that 95.1% of the variation in performance is influenced by the three main variables in the model, while the remaining 4.9% is influenced by factors outside this study. To improve the performance of private banking in Palembang, management needs to adopt a holistic approach through wellness program policies and strengthening an inclusive work culture to prevent burnout. In addition, regular workload audits and improving leadership quality through leadership by example are needed to maintain motivation. By aligning incentive systems, mentor quality, and support for mental health, banks can create a more solid, productive, and sustainable work environment.